1978
DOI: 10.1136/bmj.2.6146.1198
|View full text |Cite
|
Sign up to set email alerts
|

Psychomimetic effects of pentazocine and dihydrocodeine tartrate.

Abstract: a diet sheet in English had had the diet satisfactorily explained compared with three out of four who received a sheet in the native language and seven out of the I 1 who received a sheet in both languages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Agitation and hypomania have been described with the use of meberidine [20]. Taylor et al [21] reported hallucinations and marked euphoria, occurring in 10% and 4% of general hospital patients taking pentazocine and dihydrocodeine, respectively. Both reports noted that these symptoms are often underreported or misattributed, often to functional psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%
“…Agitation and hypomania have been described with the use of meberidine [20]. Taylor et al [21] reported hallucinations and marked euphoria, occurring in 10% and 4% of general hospital patients taking pentazocine and dihydrocodeine, respectively. Both reports noted that these symptoms are often underreported or misattributed, often to functional psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%
“…Psychomimetic reactions in the form of vivid dreams, disorientation, hallucinations, and panic occur in up to 10% of patients taking pentawcine; this appears to be related to pentawcine's affinity for the sigma opioid receptor. 13 Occasionally, pentawcine is abused in combination with the antihistamine tripelennamine hydrochloride (known as ''T's and blues"). Consequently, penrawcine is now available in combination with low-dose naloxone hydrochloride (Talwin Nx); this formulation allows retention of its analgesic effect but offiets its illicit use.…”
Section: Michaelmentioning
confidence: 99%
“…11,16,65,66 All drugs in this class precipitate withdrawal and return of pain in patients stabilized on the pure narcotic agonists. For this reason, patients should not receive an agonist with partial antagonist activity concomitantly with a pure agonist.…”
Section: "If I Look At One Point On the Wall Above The Clock And Concmentioning
confidence: 99%